2013
DOI: 10.1016/j.jamcollsurg.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficacy of Portal Vein Embolization for Patients with Extensive Liver Malignancy and Very Low Future Liver Remnant Volume, Including a Comparison with the Associating Liver Partition with Portal Vein Ligation for Staged Hepatectomy Approach

Abstract: Background The primary reported indication for the Associating Liver Partition with Portal vein Ligation for Staged hepatectomy (ALPPS) technique is in patients with very low future liver remnant volumes. Given the elevated incidence of major morbidity (40%) and liver-related mortality (12%) with ALPPS, we sought to determine the safety and efficacy of percutaneous portal vein embolization (PVE) in a similar patient population. Patients and Methods Tumor resectability and morbidity/mortality rates were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(194 citation statements)
references
References 26 publications
7
173
0
14
Order By: Relevance
“…Patients were carefully screened for double reporting. inclusion criteria (1,2,8). All studies were retrospective.…”
Section: Types Of Outcome Measuresmentioning
confidence: 99%
“…Patients were carefully screened for double reporting. inclusion criteria (1,2,8). All studies were retrospective.…”
Section: Types Of Outcome Measuresmentioning
confidence: 99%
“…So they recommended that percutaneous PVE and interval surgery remained the standard of management for patients with low FLR volume. 21 Furthermore, Schadde et al drawed conclusions from 202 cases that incidence of severe complications including mortalities (Clavien-Dindo ≥IIIb) was 27% while Ninety-day mortality was 9% (19/202). 3 They also found that the red blood cell transfusion, ALPPS stage I operating time greater than 300 minutes, age more than 60 years, and non-CRLM were all Independent factors for severe complications.…”
Section: The Safety and Short-term Outcomes Of Alppsmentioning
confidence: 99%
“…Occlusion of the portal vein branches supplying the tumor-bearing segments results in atrophy of these segments and compensatory growth of the contralateral segments. With this technique the size of the FRLV can be increased up to 62 % of the original FRLV [5,6].…”
Section: Liver Regeneration After Partial Hepatectomymentioning
confidence: 99%